L’ús dels diccionaris escolars - Battaner, M. Paz (Caplletra. Revista Internacional de Filologia, 2015)
From a study of four cases of real use of school dictionaries a review is made of issues habitually debated in general lexicography which are present particularly in the lexicography of first-language acquisition. Proposals are then made for the use of school dictionaries as a series of learning goals based on parallel reflection on the lexical unit, and an awareness of the assumptions involved in lexicographic conventions.